Ethics, Economics and Sustainability - O'Neill J (Cambridge University Press on behalf of The Royal Institute of Philosophy, 2022)
On the dominant economic approach to environmental policy, environmental goods are conceptualised as forms of capital that provide services for human well-being. These services are assigned a monetary value to be weighed against the values of other goods and services. David Wiggins has offered a set of arguments against central assumptions about the nature of well-being, practical reason and ethical deliberation that underpin this dominant economic approach. In this paper I outline these arguments and consider their implications for understanding ethical demands across generations. The paper focuses, in particular, on their implications for understanding the nature and requirements of sustainability.